PENCIPTAAN BUKU REFERENSI SITUS GAPURA BAJANG RATU SEBAGAI UPAYA PELESTARIAN WARISAN BUDAYA MAJAPAHIT - Wijaya, Eka Satriawan Kusuma; Bahruddin, Muh; Hidayat, Wahyu (Jurnal Art Nouveau, 2015)
Abstract: Seeing the development of modern times many heritage buildings in Mojokerto, one of which is building the temple. The problem, of the Temple is not widely known by the society. This is because not many media who publishes, in particular through the book. Though the temple is the nations cultural heritage which must be preserved so well known by future generations. See background Mojokerto city known as the historic city of Mojokerto certainly has a lot of heritage, one of which is the Temple. The temple is a relic of the king, who has served in that age. With a relatively old age is certainly temple has historical value and the philosophy behind the establishment of the building and it can not be forgotten, especially by residents of the town of Mojokerto. In this study shows how the history of the Gate Bajang Ratu and relief of the Gate Bajang Ratu.Â Keywords: Temple Trowulan, Design, Heritage, Reference Book, Preservation